Keeping students in by sending them out: Retention and service-learning - Iris Mae Yob (Laureate Education Inc, 2014)
This review of recent literature examines the research on the impact of service-learning on student retention.  The theoretical framework of the review draws on both Tinto's model of student attrition and Knowles's theory of adult learning, which together suggest that academic and social integration, active participation and engagement in learning, and application and relevancy of the subject-matter under study are key factors in student success. The role of these factors has been confirmed in a growing body of research around learning experiences in general and, as this review shows, particularly in service-learning experiences. Suggestions are made for how future research might expand and critically deepen this evidence and offers some implications for service-learning as a means of improving student retention. DOI: 10.18870/hlrc.v4i2.177